Twelve-week exercise training and the quality of life in menopausal women – clinical trial - Dąbrowska, Jolanta; Dąbrowska-Galas, Magdalena; Rutkowska, Magdalena; Michalski, Bogdan Adam (Menopause Review/Przegląd Menopauzalny, 2016)
Introduction: The menopause transition is associated with decreased health functioning. About 80-90% of women experience mild to severe physical or physiological menopause-related complaints per year when approaching menopause. Physical activity may reduce some climacteric symptoms and improve the quality of life. Aim of the study was to investigate the influence of a 12-week training programme on the quality of life (QoL) in menopausal-aged women living in a rural area. Material and methods: Participants were 80 women aged 40-65 years and divided into two randomly selected groups in training sessions (exercising group, n = 40 and control group, n = 40). SF36 was used to assess the quality of life in both groups before and after 12 weeks. Exercising women participated in training session 3 times a week. Each 60-minute exercise session included warming-up exercises, walking, stretching, strengthening exercises with an elastic band and cooling down exercises. Results : A non-significant positive difference in all SF36 domains in the exercising group was observed. The results of the study showed a statistically significant higher QoL in the exercising group compared to the control group after 12-week training in two domains: vitality and mental health. The improvement in the quality of life in the study group was 0.19 points (role limits – physical domain, least change) and 4.96 (vitality domain, most change). Conclusions : Controlled and regular exercise for 12 weeks was significantly correlated with a positive change in vitality and mental health. Sedentary women should consider modification of their lifestyle to include physical activity as it leads to improvement of their quality of life.